"We are All Artists of Our Lives": A Conversation with Romesh Gunesekera - Rocío G. Davis (Miscelánea: A Journal of English and American Studies)
In this interview, the British writer Ramesh Gunesekera (Sri Lanka, 1954), poet and writer of fiction, speaks of his writing, focusing on his novel Reef, shortlisted for the Booker Prize in 1995, and its artistic treatment of life experience, memory and identity.